PERANAN IDA PEDANDA MADE SIDEMEN DAN IDA PEDANDA MADE KEMENUH DALAM MENINGKATKAN SRADHA DAN BAKTI UMAT HINDU - Suweta I Made (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Hindu priests in Bali have an important role in the concept of the pupils. In the concept of the pupils contained the meaning of the relationship between teachers and students. What is meant by teachers in this case is the pastor, while the intended disciple is a Hindu who needs the spiritual guidance services of the priest in question. Associated with the relationship of the students there is a masurya term that merupankan esteem as a priest honor the bonds of the relationship of the students. While the term solar as a denominator of the pastor is a pronoun of honor to the pastor as a spiritual teacher. The formulation of the problems that need to get the discussion as follows: (1) How Hindu priests exist as capable of ceremonial leaders and provide a religious quality in the transformation of Balinese culture ?, (2) What is the form of Hindu priests’ activity in improving the quality of Hindu religiousity in Balyarsakat Bali? ) How is the role of the Hindu priest in the effort to improve the quality of Balinese Hindu religiosity? Each research activity is inseparable from the desired goal. Similarly, this research has the following research objectives: (1) To know the existence of the phenomenon of changing various aspects of socio-culture of Balinese society as a logical consequence of modernisation, globalization, and economic transformation, (2) To know the importance of socialization of Hindu religion values Which is reflected in the teachings of philosophy, ethics, and ceremonies as an anticipatory step for the Balinese in the cultural trasisi period; From agrarian culture to industrial culture and modernization, and (3) to know how far the function of Hindu priests in trying to give the weight of Balinese faith. Anything as the findings of this study is as described below. Ida Made Sidemen and Ida Made Made Kemenuh are two prominent Hindu figures who have concretely worked in a concerted effort to give a weight of faith to the Hindu community in Bali. Ida Pedanda Made Sidemen gives the weight of faith to the Hindu community in Bali through literary works. While Ida Pedanda Made Kemenuh disseminate the beliefs of faith to the Hindu community through religious lectures (dharma discourse). From the literary works of Ida Pedanda Made Sidemen is studied the conception of faith from the manuscript of his work (1) Kidung Pisacarana, (2) Kakawin Candraberawa, and (3) Geguritan Salampah Laku. While Ida Pedanda Made Kemenuh studied the conception of the faith of his lectures on (1) Fungsi Agama, (2) Dasa Sila Hindu Bali, and (3) Fungsi Pura. Keywords: Pastor, Faith, Religious Quality